Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Produktivitas Karyawan - Novi Tanti; Ica Rahayu Situmorang (Journal of Information Systems and Management (JISMA), 2023)
In achieving company goals, quality human resources and high work productivity are needed. Every company will always try so that the employees involved in these activities can contribute in the form of the highest possible work productivity to realize the goals that have been set. Company culture and work environment certainly also affect work productivity. With high work productivity, employees are expected to be more effective and efficient. Building an organizational culture is certainly not easy, it must go through a long and continuous process. It is called sustainable because the values and norms that exist in culture are constantly changing and developing according to the times. High discipline attitude is needed in order to achieve organizational goals. The purpose of this study is to find out and analyze how the influence of organizational culture and work environment on employee productivity.